Transformation of miemroaantrients as influenced by tillage, water and integrated nutrient managemeat erander rice (Oyza sativa) -wheat (Triticum aesfiv~m)c ropping system* - BISWAS, HRITTICK; RATTAN, R K; SINGH, A K (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was carried out during 20011-2002 to assess the changes in DTPA-extractable micronutrient status of a soil at different stages of a rice (Oryza sativa L.) -wheat (Triticum aestivum L. emend. Fiori & Paol) cropping system, as brought about by different combinations of tillage, water and nutrient management.Puddling and continuous submergence had a synergistic effect on the availability of DTPA-extractable iron, manganese and copper to rice crop but decreased zinc availability. After completion of one cycle of nice-wheat there was a decline, in the micronutrient status of the soil. While application of farmyard manure and Leucaena slowed down ths decline, all the micronutrients under study increased on application of sewage-sludge.